Respuesta :
Answer with step-by-step explanation:
1) Inverse of [tex]f(x) = 6x -24[/tex]:
Make the function equal to y to get [tex]y=6x-24[/tex].
Now making [tex]x[/tex] the subject of the function:
[tex]6x=y+24\\\\x=\frac{y+24}{6} \\\\x=\frac{y}{6} +4[/tex]
Change back the variable [tex]y[/tex] to [tex]x[/tex] and this is the inverse.
[tex]f'(x)=\frac{x}{6} +4[/tex]
2. Inverse of [tex]g(x) = 3x^2 - 5[/tex]:
Making the function equal to y to get: [tex]y=3x^2 - 5[/tex]
Now making [tex]x[/tex] the subject of the function:
[tex]3x^2=y+5\\\\x^2=\frac{y+5}{3}[/tex]
Taking square root on both sides to get:
[tex]x=\sqrt{\frac{y+5}{3} }[/tex]
Change back the variable [tex]y[/tex] to [tex]x[/tex] and this is the inverse.
[tex]g'(x)=\sqrt{\frac{x+5}{3} }[/tex]
Answer:
1) [tex]f^{-1}(x)=\frac{x}{6}+4[/tex]
2) [tex]g^{-1}(x)=\sqrt{\frac{x+5}{3}}[/tex]
Step-by-step explanation:
1) To find the inverse of the function [tex]f(x) = 6x -24[/tex] you need to follow these steps:
- Since [tex]f(x)=y[/tex], you can rewrite the function:
[tex]y = 6x -24[/tex]
- Solve for "x":
[tex]y+24=6x\\\\x=\frac{y+24}{6}\\\\x=\frac{y}{6}+4[/tex]
- Exchange the variables:
[tex]y=\frac{x}{6}+4[/tex]
Then, the inverse is:
[tex]f^{-1}(x)=\frac{x}{6}+4[/tex]
2) To find the inverse of the function [tex]g(x) = 3x^2 - 5[/tex] you need to follow these steps:
- Since [tex]g(x)=y[/tex], you can rewrite the function:
[tex]y= 3x^2 - 5[/tex]
- Solve for "x":
[tex]y= 3x^2 - 5\\\\\frac{y+5}{3}=x^2\\\\x=\sqrt{\frac{y+5}{3}}[/tex]
- Exchange the variables:
[tex]y=\sqrt{\frac{x+5}{3}}[/tex]
Then, the inverse is:
[tex]g^{-1}(x)=\sqrt{\frac{x+5}{3}}[/tex]